TAMAN MENGAJI ACTIVITY PROGRAM FOR THE SUCCESSORS OF THE UMMAH IN ISLAMIC EDUCATION IN EARLY CHILDHOOD IN PAHLAWAN VILLAGE, TANJUNG TIRAM DISTRICT, BARA REGENCY - Zannatunnisya Zannatunnisya; Fuji Rahmadi P; Salma Rozana (Proceeding International Seminar of Islamic Studies, 2023)
Early childhood is a golden age where at this time is the time when children must get the best education, especially Islamic religious education where guidance in the form of body and soul will strengthen the child's personality and faith at an early age. Thus all the efforts of parents will provide education to shape the child into a sholeh and sholehah child. Taman Mengaji Penerus Umat is a religious activity given to the community, especially in early childhood, where this activity will help children to get to know religious education more deeply by studying iqra, prayer practices, moral guidance, and Friday alms activities that are carried out regularly in The Hero Village, Tanjung Tiram District, Batu Bara Regency. Through religious activities, it aims to make children have akhlaktulkarimah, have an exemplary attitude, think positively according to Islamic teachings. Where Islamic education plays an important role in the future of children. The guidance activities of the garden to study the successor of the people (TMPU) are very helpful for the community in educating children by being guided by competent teachers in the field of Islamic religious education